Energy efficient and QoS aware routing protocol for Clustered Wireless Sensor Network - Nazir, B. (2013)
In this paper, a protocol called Energy Efficient and QoS aware Routing (EEQR) protocol for Clustered Wireless Sensor Network is proposed. To ensure QoS for different traffic types, prioritization of data is done based on message type and content. To address energy efficiency (hotspot problem) and high end-to-end delay problem, a combination of mobile and static sink is used for data gathering. Delay sensitive message are sent through the static sink and delay tolerant message are send through the mobile sink. Consequently, EEQR incurs less end-to-end delay, is energy efficient as well as able to ensure QoS. To evaluate the performance of the proposed strategy, intensive simulations are carried out. Performance of the proposed strategy is compared with the static sink and mobile sinks strategies. The results demonstrated that EEQR has prolonged the network and coverage lifetime, as well as has improved the other QoS routing parameters, such as delay, packet loss ratio, and throughput. Â© 2013 Elsevier Ltd. All rights reserved.